POLISH HOUSING COOPERATIVES WILL BE ABLE TO CARRY OUT TASKS AS A CIVIC ENERGY COMMUNITY - Pałka, Piotr (International Journal of Cooperative Law, 2024)
The European Union is implementing a transformation process towards the widespread use of green energy. The implementation of the activities is long-term and is to be completed by 2050. This is when the EU area is to become a model example of a zero-emission economy prepared also for the Polish housing cooperatives which will be able to carry out tasks as a civic energy community.